SELECTIVE TEXTUAL EVIDENCE AS A CASE FOR A SINGLE TRANSLATOR OF ATHANASIUS' ORATIONS AGAINST THE ARIANS INTO OLD SLAVONIC. - LYTVYNENKO, Viacheslav V. (Slovo (05836255), 2018)
This study makes a case for a single Slavonic translator of Athanasius' Orations against the Arians and the Epistle to the Bishops of Egypt and Libya (treated as the fourth Oration in the Old Slavonic corpus). For this purpose, it examines eight Greek terms and their Slavonic equivalents that represent the most basic terminology in the vocabulary of the fourth-century trinitarian debates and Athanasius' Orations. The first part of this study provides a terminological table organized around the thematic rubrics, and it is meant to be exhaustive, covering all four writings. The second part provides an analysis of the selected terms based on the data in the terminological table. It explores the patterns of consistency in the way these terms are used throughout the Orations and offers the arguments for why the Slavonic Orations can be perceived as the work of a single translator.